Corporate brand personality re-focus your organization's culture to build trust, respect and authenticity - Everett, Lesley (Kogan Page Limited, 2016)
"Corporate Brand Personality addresses the increasing need for organizations to refocus and realign their corporate culture in order to compete in a business world that demands trust, respect, and strong values. Moving beyond simply how products are marketed and perceived, it explains how to lead and engage people at every level within the organization to ensure consistent engagement with brand values. Including practical models to show how corporate culture and values can be managed and improved, author Lesley Everett provides real examples and case studies from sectors including hospitality, engineering, retail, and finance that show how employees' behaviors can deeply affect brand reputation through all areas of the organization. Incorporating a complete strategy from start to finish, this book will help managers and HR directors build visible leadership, project an authentic brand image, and reinforce the company's values. Corporate Brand Personality addresses the increasing need for organizations to refocus and realign their corporate culture in order to compete in a business world that demands trust, respect and strong values. Moving beyond simply how products are marketed and perceived, it shows the reader how to lead and engage people at every level within the organization to ensure consistent engagement with brand values. Including practical models to show how corporate culture and values can be managed and improved, Corporate Brand Personality also provides real examples and case studies from the Marriott Hotel Group and Water Wellbeing Group among others that show how people's behaviours can deeply affect brand reputation through all areas of the business. Incorporating a complete strategy from start to finish, this book will help the reader build visible leadership, project an authentic brand image and reinforce their company's values"--Provided by publisher.